2021
DOI: 10.1002/ptr.7151
|View full text |Cite
|
Sign up to set email alerts
|

Natural products and phytochemicals as potential anti‐SARS‐CoV‐2 drugs

Abstract: The current pandemic responsible for the crippling of the health care system is caused by the novel SARS‐CoV‐2 in 2019 and leading to coronavirus disease 2019 (COVID‐19). The virus enters into humans by attachment of its Spike protein (S) to the ACE receptor present on the lung epithelial cell surface followed by cleavage of S protein by the cellular transmembrane serine protease (TMPRSS2). After entry, the SARS‐CoV‐2 RNA genome is released into the cytosol, where it highjacks host replication machinery for vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 101 publications
(197 reference statements)
0
57
0
Order By: Relevance
“…Many plant-derived molecules have been studied using computational approaches (docking and dynamic studies) targeting SARS-CoV-2 key enzymes including papainlike proteases (PLpro), 3C-like protease (Mpro) and NSP15 proteins. Several molecules have been reported to bind to active site of these three SARS-CoV-2 proteins with high binding affinity [41][42][43][44][45][46][47][48]. In silico studies have shown that various natural products have strong binding affinity to the non-structural proteins of SARS-CoV-2 virus (PLpro, Mpro and RdRp), and structural proteins such as spike (S) protein [43,49].…”
Section: Target Predictionmentioning
confidence: 99%
“…Many plant-derived molecules have been studied using computational approaches (docking and dynamic studies) targeting SARS-CoV-2 key enzymes including papainlike proteases (PLpro), 3C-like protease (Mpro) and NSP15 proteins. Several molecules have been reported to bind to active site of these three SARS-CoV-2 proteins with high binding affinity [41][42][43][44][45][46][47][48]. In silico studies have shown that various natural products have strong binding affinity to the non-structural proteins of SARS-CoV-2 virus (PLpro, Mpro and RdRp), and structural proteins such as spike (S) protein [43,49].…”
Section: Target Predictionmentioning
confidence: 99%
“…44 The COVID-19 pandemic presents an unprecedented challenge to the healthcare system globally and causes a huge stress on the economy worldwide. 72,74 SARS-CoV-2 has glycoprotein spikes projecting from its envelope, giving it a crown-like structure. 71,74 Four structural proteins, spike glycoprotein (S), small envelope glycoprotein (E), membrane glycoprotein (M) and nucleocapsid protein (N) and 16 non-structural proteins have been identified.…”
Section: Role Of Mcs In Coronavirus Infectionmentioning
confidence: 99%
“…Coronaviruses are single positive‐strand, enveloped ribonucleic acid viruses. 71 , 72 Within the last 20 years, there have been three highly pathogenic, zoonotic diseases caused by coronaviruses, with Severe Acute Respiratory Syndrome (SARS‐CoV‐1) first being detected in China in 2002 and then Middle East Respiratory Syndrome coronavirus (MERS‐ CoV) in Saudi Arabia in 2012, both caused outbreaks and spread globally. 71 , 73 , 74 There were more than 8000 SARS‐CoV‐1 cases with about 10% mortality rate whereas MERS‐CoV had about 2500 cases and an almost 40% mortality rate.…”
Section: Role Of Mcs In Coronavirus Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…In spite of the fact that numerous drugs do exist that have clinically proven antiviral properties (Indari et al, 2021) and several drugs that show a limited potential to alleviate COVID-19 symptoms (Lam et al, 2020;Raju et al, 2021), none of them have proven to work efficiently to reduce COVID-19 associated mortality. Nevertheless, several in vitro studies have demonstrated the potential of several phytochemicals to inhibit COVID-19 infectious cycle in humans at various stages (Alam et al, 2021;Behl et al, 2021;Marmitt et al, 2021;Merarchi et al, 2021). These phytochemicals have been demonstrated to inhibit viral entry, viral replication, or viral release -in addition to attenuating the host pathological responses (Figure 2).…”
Section: Covid-19 Virus and Its Life Cyclementioning
confidence: 99%